Security in the Area of Culture as Viewed by the European Union - Gołda-Sobczak, Maria (Przegląd Strategiczny, 2016)
The European Communities, later the European Union, for a long time did not pay attention to the protection of European cultural heritage, as well as to issues o f cultural policy, leaving the area more or less consciously the Council o f Europe. The cultural policy o f the European Union treats the ambiguous term “culture” as an area that belongs to the sphere of national sovereignty. Undefined terms from the area of culture, such as the European cultural space, a common cultural heritage, etc. appear in the documents o f the European Union. Only Art. 151 o f the Treaty establishing the European Community, currently Art. 167 of the Treaty on the functioning o f the European Union is more specifically devoted to the issue of culture and more closely to the issue of heritage. The cultural policy on this ground includes the protection o f European cultural heritage, undertaking projects involving the development of a culture and the promotion of European culture. In that respect, the attention should be paid to a number of bilateral agreements, international programs, and finally conventions.